Virtual inertia emulation through virtual synchronous generator based superconducting magnetic energy storage in modern power system. (15th December 2021) - Salama, Hossam S.; Bakeer, Abualkasim; Magdy, Gaber; Vokony, Istvan
Highlights: Propose a SMES system-VSG power management. Propose active power control and voltage control. SMES is used to imitate the needed inertia power from the VSG in a short period to handle issues of high RESs penetration.. The implementation of the SMES-based VSG can compensate the unbalanced power as well as frequency/voltage fluctuations. VSG-based SMES is important to compensate for the power system and eliminate frequency and voltage fluctuations. Abstract: Recently, renewable energy sources (RESs) have been integrated into modern power systems using power electronic converters, which have null inertia properties. The main issue for this integration is the total inertia of the power system will be decreased, and the system stability will be prone to collapse. So, it is urgent to save a source for virtual synchrotrons generator (VSG) to compensate for the reduction in conventional sources and keep on the frequency and voltage stability. The main idea of VSG needs an energy storage system (ESS) with converters to emulate virtual inertia like the dynamics of traditional synchronous generators. Therefore, this paper proposes a VSG accompanied by superconducting magnetic energy storage (SMES), that has a fast response compared to other ESS. The proposed method feeds the modern power system with inertia during unpredictable events and improves the frequency and voltage response. The command active power of the SMES system is computed according to the state of the frequency deviation in the VSG model with a PI-controller, considering the virtual inertia and damping factors. Meanwhile, reactive power control is achieved by Voltage control. The obtained results based on MATLAB/Simulink prove the effectiveness of the proposed method to support the modern power system with inertia and improving the transient and steady-state behavior of frequency and voltage.